Software-Defined 1550-nm Full-Fiber Doppler Lidar for Contactless Vibration Measurement of High Voltage Power Equipment - Guan, X.; Lv, C.; Zheng, G.; Pan, Z.; Cai, K. (Společnost pro radioelektronické inženýrství, 2023)
In this work, a 1550-nm full-fiber Doppler lidar via software-defined platform is built to realize flexible and low-cost contactless vibration measurement of high-voltage power equipment. A 1550-nm fiber layout is designed to generate optical interference between vibration signal and carrier wave. The reflected vibration signal is collected by an optical transceiver and the carrier wave is generated by an acousto-optic modulator (AOM). The optical beat signal is collected by a balanced detector (BD) then sent into a general software defined radio (SDR) receiver. By GNU developing platform, the target mechanical vibration signal is demodulated and several flexible functions such as speed-acceleration trans, harmonic component analysis and fault diagnosis is realized. Performance of Doppler lidar is first verified on mechanical vibration source by PZT vibration actuator, results show that the designed lidar could retrieve 50 Hz–20 kHz mechanical vibration signals within the working distance is up to 20 m. Further case application scenarios on the power transformer and gas-insulated switchgear (GIS) are also conducted to verify the feasibility of proposed lidar.
Keywords: Doppler; lidar; vibration detection; power equipment; software-defined